EFFECTS OF LASER RADIATION ON THE KINETICS OF PHYSICAL AND CHEMICAL TRANSFORMATION OF POLYMERS - and (Municipal economy of cities. Series: «Economy science», 2013)
Consider physical modification of polymers laser to reduce their flammability shows experimental research methods and analysis UV and IR spectra film epoxy compositions.